PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAK PIDANA MANIPULASI DATA PRIBADI SECARA ELEKTRONIK (STUDI PUTUSAN NOMOR:105/PID.SUS/2019/PN-PBR) - Muhammad Agustiawan; Alpi Sahari (JURNAL DOKTRIN REVIEW, 2023)
Information technology is currently a double-edged sword because apart from contributing to increasing human welfare, progress and civilization, it is also an effective means of unlawful acts including criminal acts (crimes). This study aims to analyze legal protection for victims of the crime of electronic personal data theft, the modus operandi used in the crime of electronic theft of personal data and legally analyze the crime of electronic manipulation of personal data in Decision Number: 105/Pid.Sus/ 2019/PN-Pbr. This research method uses normative research. Based on the results of this study, the finesanction still has confusion, meaning whether the fine came from the loss suffered by the victim or whether the fine was only the result of an act committed by the defendant based on the article imposed on the defendant. In the aquo case regarding fines, the judge imposed a fine on the defendant